Music-guided imagination technology combined with acupoint application therapy and Traditional Chinese Medicine nursing measures for preoperative blood pressure control in a patient with thoracic aortic ulcer (运用引导性音乐想象技术及穴位贴敷疗法改善1例主动脉溃疡患者术前血压的中医护理体会) - HOU Xuemin (侯雪敏); HUANG Yanping (黄砚萍); FANG Xiaomei (方晓梅) (中西医结合护理)
This paper summarized the preoperative nursing practice of a patient undergoing endovascular exclusion for thoracic aortic ulcer. Guided by the theory of Traditional Chinese Medicine emotion regulation, the music-guided imagination technology combined with acupoint application therapy by syndrome differentiation were carried out to control the blood pressure of the patient before surgery. After active treatment and nursing, the patient recovered smoothly and was discharged from the hospital. (本文总结1例胸主动脉溃疡患者行腔内隔绝术术前的中医护理体会。以中医情志护理为指导, 对患者辨证分析, 应用引导性音乐想象技术及穴位贴敷疗法对其术前血压进行干预, 经过积极救治与护理, 患者手术顺利, 术后康复出院。)